Validation of Image Quality and Diagnostic Accuracy Using a Mobile Phone Camera Microscope Adaptor Compared With Glass Slide Review in Teledermatopathology. (May 2020) - Laggis, Caroline W.; Bailey, Elizabeth E.; Novoa, Roberto; Stewart, Campbell L.; Stoff, Benjamin; Wanat, Karolyn A.; Barbieri, John; Kovarik, Carrie
Abstract : Abstract: New modalities of evaluating histopathology, such as whole-slide imaging, have been validated in the field of dermatopathology but are often unfeasible and unavailable in developing countries. Widely available across the globe, mobile phone camera technology represents a potential simple and inexpensive method of imaging histologic slides through the use of a mobile phone camera microscope adaptor. This study aims to validate the use of a commercially available adaptor in the diagnosis of inflammatory and infectious conditions in dermatopathology. Representative images were taken of slides for fifty-four cases using the adaptor and shared through a cloud-based platform with five dermatopathologists who rendered diagnoses and judged the quality of the images. After a washout period of 8 weeks, the same cases were assessed by the same dermatopathologists using the original glass slides. The intraobserver concordance rate was 93.3%, and the quality of the mobile phone images was rated as "excellent" or "diagnostic" in 94.4% of the cases. This study validates the use of this low-tech and low-cost adaptor as a reliable tool in teledermatopathology. Limitations of the study include those inherent to use of the adaptor and the limited panel of diagnoses. The primary value of this device may be in developing countries, but its practicality and ease of use lend itself to use in academic and consultative settings in the developed world as well.